The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1603/ec12349
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Cytochrome P<SUB>450</SUB> Activity in Field Populations of <I>Cydia pomonella</I> (Lepidoptera: Tortricidae) Resistant to Azinphosmethyl, Acetamiprid, and Thiacloprid

Abstract: The Río Negro and Neuquén Valley is the most important apple and pear growing region in Argentina. Cydia pomonella L. (Lepidoptera: Tortricidae), the main fruit-tree pest is being controlled by azinphosmethyl (AzMe), acetamiprid (Acet), and thiacloprid (Thia) among other insecticides. The objective of this study was to evaluate the response of neonate larvae of codling moth to these three insecticides and on the role of cytochrome P450 monooxygenase in their toxicity. All field populations presented significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 40 publications
0
13
0
1
Order By: Relevance
“…The Ncyano-imino neonicotinoids thiacloprid and acetamiprid, are relatively effective for codling moth control and have been widely adopted since their introduction. Resistance to both compounds has been reported in C. pomonella populations from Europe [92,93], the U.S. [94] and Argentina [95], with low level resistance to thiacloprid also reported in populations from Canada [96]. Surprisingly, resistance to thiacloprid in Europe has been observed in countries/regions prior to their use by growers and this is associated with cross-resistance with older compounds.…”
Section: Other Pestsmentioning
confidence: 99%
“…The Ncyano-imino neonicotinoids thiacloprid and acetamiprid, are relatively effective for codling moth control and have been widely adopted since their introduction. Resistance to both compounds has been reported in C. pomonella populations from Europe [92,93], the U.S. [94] and Argentina [95], with low level resistance to thiacloprid also reported in populations from Canada [96]. Surprisingly, resistance to thiacloprid in Europe has been observed in countries/regions prior to their use by growers and this is associated with cross-resistance with older compounds.…”
Section: Other Pestsmentioning
confidence: 99%
“…). Previous results on neonates from this FP showed increased mean ECOD activity, although not statistically significant (Cichón et al ., ). However, both FPs of diapausing larvae and neonates from the region have shown more than 4 fold higher activity than the one from LSS.…”
Section: Discussionmentioning
confidence: 97%
“…Previous research on neonates from this FP showed significant lower mortality to azinphosmethyl, acetamiprid and thiacloprid compared to the LSS. At the diagnostic concentrations (LC 99 ) of azinphosmethyl (2 mg/L), acetamiprid (0.7 mg/L) and thiacloprid (1 mg/L), the percentage of FP mortalities was 16.9, 51.1, and 14.8; respectively (Cichón et al ., ). Decreased toxicity to azinphosmethyl was also found in diapausing larvae of C. pomonella across the Río Negro and Neuquén Valley compared to the LSS (Soleño et al ., , ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…affects mainly apple production [1]. As a result of long-term pesticide use, the codling moth has developed resistance to different insecticide modes of action and chemistries, such as neurotoxic insecticides and insect growth regulators [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18], and even to C.…”
Section: Accepted Manuscriptmentioning
confidence: 99%